Survival Strategy under Pressure: Expenses Retrenchment, Assets Retrenchment and Free Assets on Financial Turnaround of Negative Equity Companies on the IDX (2022-2024) - Ida Ayu Fatmayuni; Sri Dwi Ari Ambarwati; Dorothea Ririn Indriastuti; Aditya Wardana (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effects of expense retrenchment, asset retrenchment, and free assets on the probability of financial turnaround in companies with negative equity listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The research begins by identifying firms with negative equity, followed by classifying those experiencing financial distress using the Altman Z-Score model. The sample comprises 46 companies selected through purposive sampling, based on the criterion of having published at least one annual report within the study period. Panel logistic regression is employed in this model using STATA software. The findings demonstrate that free assets have a statistically significant and positive influence on the likelihood of a financial turnaround. This suggests that firms with a higher proportion of unencumbered or readily available assets are better positioned to respond flexibly and swiftly to financial distress without resorting to cost-cutting or asset liquidation. Conversely, expense and asset retrenchment strategies do not show a significant impact, indicating that such measures alone may be insufficient to drive recovery in the absence of adequate financial buffers. This study is limited to financial variables and does not incorporate qualitative factors such as CEO characteristics. Future research is encouraged to include non-financial dimensions to enrich the understanding of effective turnaround strategies in distressed firms.